Degradation of IRAK4 for the treatment of lipopolysaccharide-induced acute lung injury in mice - Ye, Bijun; Chen, Shiyan; Huang, Xiaohao; Qiu, Yinhong; Luo, Ruixiang; Zheng, Lulu (Frontiers in Pharmacology, 2025)
Excessive pulmonary inflammation in acute lung injury (ALI) results in high patient mortality. Interleukin-1 receptor-associated kinase 4 (IRAK4) is a potential therapeutic target for inflammatory diseases. However, due to the dual functionality of IRAK4 as both an active kinase and a scaffolding protein, inhibiting its kinase activity yield moderate anti-inflammatory results. The present study explored the efficacy of KT-474, a prototypical IRAK4 degrader, which effectively diminished cellular IRAK4 levels, achieving half-maximal degradation at a concentration of 4.0 nM in RAW 264.7 cells. KT-474 effectively inhibited the activation of downstream nuclear factor (NF)-κB signaling, exhibiting stronger pharmacological impacts compared to conventional kinase inhibitors. Additionally, a lipopolysaccharide-induced acute inflammatory mouse model was established, and KT-474 displayed significant therapeutic benefits in vivo compared to kinase inhibitors. Therefore, these findings highlight the therapeutic potential of IRAK4 degrader for the treatment of acute lung injury.